2013
DOI: 10.1371/journal.pone.0072633
|View full text |Cite
|
Sign up to set email alerts
|

Association between MGMT Promoter Methylation and Non-Small Cell Lung Cancer: A Meta-Analysis

Abstract: BackgroundO6-methylguanine-DNA methyltransferase (MGMT) is one of most important DNA repair enzyme against common carcinogens such as alkylate and tobacco. Aberrant promoter methylation of the gene is frequently observed in non-small cell lung cancer (NSCLC). However, the importance of epigenetic inactivation of the gene in NSCLC published in the literature showed inconsistence. We quantified the association between MGMT promoter methylation and NSCLC using a meta-analysis method.MethodsWe systematically revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 26 publications
4
44
0
Order By: Relevance
“…72 Furthermore, in order to empower the precision of the diagnostic outcome of each study, several meta-analyses have been conducted. 70,[73][74][75] Taking into account the results of many individual studies, these meta-analyses confirmed that the methylation status of MGMT, 70 CDKN2A, 74 APC, 75 and RARβ 73 promoters is strongly related to lung cancer development.…”
Section: Diagnostic Markersmentioning
confidence: 60%
“…72 Furthermore, in order to empower the precision of the diagnostic outcome of each study, several meta-analyses have been conducted. 70,[73][74][75] Taking into account the results of many individual studies, these meta-analyses confirmed that the methylation status of MGMT, 70 CDKN2A, 74 APC, 75 and RARβ 73 promoters is strongly related to lung cancer development.…”
Section: Diagnostic Markersmentioning
confidence: 60%
“…Promoter methylation of tumor suppressor genes is common in body fluid and can be used as a lung cancer diagnosis method or biomarker. Several studies have evaluated its clinical application with acceptable diagnostic performance and high specificity …”
Section: Discussionmentioning
confidence: 99%
“…Promoter methylation of tumor suppressor genes is frequently detected in cancer tissue and body fluid in malignant carcinomas such as lung, colorectal, and esophageal cancers. Previous studies have reported that methylation of the P16 INK4a gene promoter is common in lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we observed a greater overlap of genes in AML and NSCLC that are associated with significantly hypomethylated CG sites and that might indicate the existance of several target genes. Some of these genes include candidate tumor suppressor genes like MGMT (37,38), THRB (39,40), L3MBTL4 (41), EDNRB (42), CDH13 (43) and TGFBR3 (44).…”
Section: Discussionmentioning
confidence: 99%